Analisis Dampak Bantuan Zakat, Infaq, dan Shodaqoh terhadap Kehidupan Mustahik di Kota Padangsidimpuan - Sarimasdly; Andrie Halomoan Daulay; Nanda Pratama Hasibuan; Restia Ananda; Yuli Eviyanti (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2026)
Based on research findings, the distribution of ZIS (Zeal and Incentive Fund) in Padangsidimpuan City, managed by BAZNAS (National Azan Agency) and LAZ (Affiliated Azan and Islamic Azan Institution), has had a positive impact on the economic, educational, and health aspects of beneficiaries, particularly in meeting basic needs. However, because the majority of assistance is still consumptive, the impact is more pronounced in the short term than in strengthening economic independence. The program's effectiveness in promoting mustahik independence is not yet fully optimal. This is due to the dominance of consumptive assistance over productive programs, and limited mentoring, funding, human resources, economic literacy, equitable distribution, and monitoring. The main supporting factors are strong community awareness and institutional capacity, while inhibiting factors center on limited resources and capacity of beneficiaries. As interpreted through the CIBEST framework, the majority of beneficiaries remain in the material poverty quadrant and have not significantly shifted to the prosperity quadrant. Practically, these findings imply the need for zakat management institutions to strengthen productivity-based programs, provide sustainable business mentoring, optimize digitalization and transparency in governance, and build synergies with the government and the community, including integrating the ZIS program with regional poverty alleviation programs, so that ZIS can transform mustahik into potential muzakki (recipients of zakat). This study has limitations, including its qualitative scope at a single location, a limited number of informants, and the lack of quantitative welfare index measurements. Therefore, further research is recommended, including quantitative measurements using the CIBEST model or the National Zakat Index, comparative studies between institutions, and longitudinal studies to assess changes in the conditions of mustahik over the long term.